2018
DOI: 10.1016/j.apenergy.2018.04.121
|View full text |Cite
|
Sign up to set email alerts
|

Wave energy resource variation off the west coast of Ireland and its impact on realistic wave energy converters’ power absorption

Abstract: Historical wave trends are studied via ECMWF's reanalyses over the 20th century. • ERA20 is calibrated via quantile-matching and validated against buoy measurements. • The wave energy resource increases over 40% off the west coast of Ireland. • A 30% surplus of AMPP is observed for different WECs due to resource variations. • Extreme events occurrence doubled, doubling the time WECs spend in survival mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 69 publications
(90 reference statements)
1
47
1
Order By: Relevance
“…On the other hand, Wave Period Ratio (WPR) described in [7,8,41] which relates the energy period to the average zero-crossing period was obtained for the trend computation of wave period. The WPR changes depending on the area of study, which, in the case of Iquique and Valparaiso, lies between 0.8 and 1.…”
Section: Computation Of the Wave Energy Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Wave Period Ratio (WPR) described in [7,8,41] which relates the energy period to the average zero-crossing period was obtained for the trend computation of wave period. The WPR changes depending on the area of study, which, in the case of Iquique and Valparaiso, lies between 0.8 and 1.…”
Section: Computation Of the Wave Energy Fluxmentioning
confidence: 99%
“…However, historical long-term variations of the wave climate have been often neglected. The authors have studied these long-term variations in the Bay of Biscay and off the west coast of Ireland in [7] and [8], respectively, analysing wave trends over the 20th century and the influence of these trends in the performance of specific WECs. In both locations, positive trends have been found, with wave height (H s ), peak period (T p ) and wave energy flux (WEF) increasing significantly over the 20th century.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of wave density, most articles have only focused on SWH, while the wave period is often neglected [43][44][45][46]. Some studies [47,48] have found that there is a positive effect of wave period on wave energy density. In this regard, this paper briefly analyzes the wave period and the distribution of 10-year average wave period, as shown in Figure 5.…”
Section: Calculate Methods Of Energy Assessmentmentioning
confidence: 99%
“…For wave energy, regions where the wave energy density is greater than 2 KW/m is considered to be an available area [24,50,51]; whereas areas with values of wave energy density larger than 20 KW/m are considered to be rich areas. There is no certain standard of lowest available wave energy density for wave energy conversion equipment [48,52]. Therefore, for the assessment of wind energy distribution, 2KW/m was selected as the minimum standard for assessing the available wave energy density in the wind energy distribution.…”
Section: Occurrences Of Exploitable Wind and Wave Energymentioning
confidence: 99%
“…The cup anemometers installed on the buildings of the University of Basque Country in Eibar enabled the development of a preliminary calibration methodology based on quantile-matching techniques that were used previously by the authors for wind energy and wave energy [25][26][27]. In the scientific literature, different calibration or bias correction techniques have been developed and compared for the analysis of several parameters, such as temperature and precipitation (see [28][29][30]).…”
Section: Quantile-mapping Calibrationmentioning
confidence: 99%